ANALYSIS OF TRADING VOLUME ACTIVITY (TVA) ON BEFORE AND AFTER THE PRESIDENTIAL ELECTION OF THE REPUBLIC OF INDONESIA (Case Study of Listed Financial Institution Companies on Indonesia Stock Exchange) - Dedi Putra; Pebrina Swissia; Taufik Taufik; Agus Panjaitan (Proceeding International Conference on Information Technology and Business, 2020)
The purpose of this study was to empirically find the Market Anomaly on the Presidential Election of the Republic of Indonesia on April 17th, 2019. The type of data in this study used secondary data. The data was data on share trading volume and number of shares outstanding on listed financial institutions in the Indonesia Stock Exchange. The sources of data in this study were obtained from yahoo finance in the form of daily stock prices, namely 30 days before and 30 days after the Presidential Election of the Republic of Indonesia on April 17th, 2019 of Listed Financing Companies in the Indonesia Stock Exchange. The method of this study was descriptive statistical test and paired-samples t test. The result of this study found that there was a difference in trading volume activity between before and after the Presidential Election of the Republic of Indonesia on April 17th, 2019 for 30 days before and 30 days after the Presidential Election of the Republic of Indonesia on April 17th, 2019.Keywords: Market Anomaly, Trading Volume Activity, Capital Market, Presidential Election